Young individuals are more stable and stand more upright when using rollator assistance during standing up and sitting down - Krafft, Frieder; Herzog, Michael; Stein, Thorsten; Sloot, Lizeth H. (Frontiers in Bioengineering and Biotechnology, 2022)
Four-wheeled walkers or rollators are often used to assist older individuals in maintaining an independent life by compensating for muscle weakness and reduced movement stability. However, limited biomechanical studies have been performed to understand how rollator support affects posture and stability, especially when standing up and sitting down. Therefore, this study examined how stability and posture change with varying levels of rollator support and on an unstable floor. The aim was to collect comprehensive baseline data during standing up and sitting down in young participants.
Gesehen am 25.01.2023